The alignment of competitive priorities, process structure, and information technology and its effect on firm performance : A study of Malaysian manufacturing firms - Hasbullah, Ashari (2008)
Gaps in the existing literature especially with respect to Manufacturing Strategies components alignment and its effect on firm performance provide the rationales to the current studies. This study examines specifically the alignment of three components of Manufacturing Strategies namely competitive priorities, structural decision represented by process structures, and infrastructural decision represented by IT applications, and their effects on firms' performance. In doing so, various relationships between the components have been examined and using Profile Deviation Method the overall alignment of the three components and its effect on performance has been assessed. A research framework was developed and five hypotheses were tested. Primary data was collected from Production or Manufacturing Managers or senior Engineers using mailed questionnaire while a case study was conducted to a company that has invested large amount to have an integrated IT applications system in place. Although the recommended sample size is 330, to ensure sufficient participation, 800 hundred questionnaires were sent out to 800 companies. 104 questionnaires were returned which represented for about 12.88 % participation rate or a representative rate of 5.2 % of the population. Four types of statistical analyses were utilized namely Descriptive, Simple T- test, Profile deviation technique, and Simple Linear Regression. The following results were obtained (i) in general the results of the hypotheses testing on the various relationships between Process Structure and Competitive Priorities, Process Structure and IT Applications, and Competitive Priorities and Process Structure did not support the hypotheses; (ii) companies understudy exhibited the pattern of the Sand Cone theory; (iii) Profile Deviation technique employed to determine the effect of alignment or misalignment on performance yielded mixed results for Product Focused companies and Process Focus Companies. The case study indicated that there were indeed misalignments between the variables under study. Limitations to the current findings were also discussed and directions for future research proposed.